Крутая дамочка, или Нежнее, чем польская панна - Вильмонт Екатерина Николаевна (Астрель, 2007)
Экземпляры: Ф6 (20160114) / Инвентарный номер: 50737 / Цена: 80.00 / Сис.шифр: Р2 / Авт.знак: В 46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6